Data on the fate of MACS® MicroBeads intramyocardially co-injected with stem cell products - Paula Müller; Ralf Gaebel; Heiko Lemcke; Gustav Steinhoff; Robert David (Data in Brief, 2017)
The data presented in this article are related to the research article “Intramyocardial Fate and Effect of Iron Nanoparticles co-injected with MACS® purified Stem Cell Products” (Müller et al., 2017) [1]. This article complements the cellular localization of superparamagnetic iron dextran particles (MACS® MicroBeads) used for magnetic activated cell sorting (MACS®). Data evaluate the time-dependent detachment of these nanoparticles from CD133+ haematopoietic stem cells (HSCs) and CD271+ mesenchymal stem cells (MSCs). Furthermore, the influence of these stem cells as well as of nanoparticles on cardiac remodeling processes after myocardial infarction (MI) was investigated. Keywords: Stem cell therapy, Cardiovascular regeneration, Haematopoietic stem cells (HSCs), Mesenchymal stem cells (MSCs), Magnetic activated cell sorting (MACS®), MACS® MicroBeads